Bacias de acumulação de águas de chuva em estradas rurais: umidade do solo e vida útil - Carvalho, Ronan Naves (2017)
The purpose of this work was to evaluate the behavior of water from volumes that would be stored in basins of accumulation along the roadside. This work was carried out in two experimental areas, the first one located in a forest area and the second area in a site with an accumulation basin adjacent to pasture areas. For the construction of the research, soil moisture monitoring was carried out after the accumulation basins, and in each area 5 soil moisture monitoring points were installed in the soil, being 0, 1, 3, 6 and 10 meters of the skirt of the basin, forming a straight axis in the direction of the water courses. The soil moisture at these points was monitored from 20 to 20 cm deep to 80 cm, and between may 2015 and april 2017 in the forest area (area 1) and from january 2016 to april 2017 in the pasture area (area 2 ), and for the collection of soil moisture data, a FDR PRIME PICO IPH3 probe from the manufacturer IMKO was used. In order to better characterize the areas, several physical and hydraulic parameters were determined, such as saturated hydraulic conductivity of the soil, soil density, particle density, porosity, and soil textural analysis. It was also performed analyzes of the geometric attributes of the basins before and after the hydrological period of rainfall in order to evaluate the useful life of the basins, for these determinations were collected field data with geodetic GPS and later worked on the software ArcGIS 9.3. Considering the data obtained, it was noticed that the soil moisture in area 1 in a temporal analysis had high variability throughout the period, ranging from 29,5% in some points in the dry periods to more than 52% in rainy periods in the area 1, and between 25% and 41.3% in area 2, highlighting the deeper layers in this area that suffered minor variations in soil water content. In addition, it is worth noting that in the two analyzed areas, during the entire evaluation period, at no moment did the soil moisture reach values lower than the values of permanent wilt point soil moisture at any point or layer. In order to observe signs of water movement in the profile of the areas studied as a result of the accumulation basins, analyzes were made of small isolated periods that consisted of isolated rainfall events followed by long periods of drought. In these analyzes, it was found that in both areas there was strong evidence that the water stored in the accumulation basins was seeping into the soil and moving towards the soil moisture monitoring points installed. In the evaluations, it was noticeable that the volume of water stored after a few days of the occurrence of precipitation and after the first "drying" of the soil, was raised again in the first points and later in the later monitoring were detected in the posterior points. Regarding the analyzes of the useful life of the basins, between the evaluated periods, calculated as a result of the volume reduction (-37,29% in area 1 and -32,93% in area 2) of the accumulation basins, it was the accumulation basin in area 1 is about 2,68 years and that of area 2 is around 3,03 years, in addition to receiving 104,2 and 35,3 m³.ha-¹.year-¹, respectively, of sediments in the intervals between the data collection campaigns. In view of the presented results, it can be inferred that the accumulation basins would be influencing the soil moisture behavior along the profile, allowing the soil to be moistened for a longer time and that would be avoiding the carrying of considerable sediment amounts for the nearby watercourses.